Economic Impact of Fisheries and Aquaculture on Rural Livelihoods: A Review - Gunjita Sinha,; Dr. Mainak Banerjee, (The Bioscan, 2025)
Fisheries and aquaculture have emerged as critical sectors in shaping rural economies, livelihoods, and food systems, particularly in low- and middle-income countries. With global fish consumption rising and capture fisheries plateauing, aquaculture now plays an increasingly central role in meeting protein demands, generating employment, and supporting sustainable income in rural regions. This review explores the multifaceted economic impact of fisheries and aquaculture on rural livelihoods through a synthesis of peer-reviewed literature, institutional reports, and regional case studies. The findings demonstrate that aquaculture contributes significantly to rural household income—ranging from 20% to 50% depending on geography and production systems—and provides employment for millions directly and indirectly through input supply, production, processing, and marketing. Women are especially active in post-harvest and informal sectors, although their contributions often go unrecognized and undervalued in formal economic assessments. Additionally, aquaculture investments frequently lead to asset accumulation and rural infrastructure development, creating long-term socio-economic benefits. This review also identifies critical barriers such as access to finance, market integration, gender inequality, and vulnerability to environmental changes. It highlights policy interventions, technology adoption, and cooperative models that have demonstrated success in improving outcomes. The article concludes by emphasizing the importance of inclusive, gender-sensitive, and climate-resilient aquaculture development strategies to enhance its role in rural transformation and poverty alleviation. By offering a comprehensive overview of economic contributions, employment dynamics, gender roles, and policy implications, this review provides valuable insights for researchers, policymakers, and development practitioners working to leverage fisheries and aquaculture for rural development.